Enhanced UV Light‐Emission of Zinc‐Phosphate‐Hydrate Hydrothermally‐Grown on Cu Metal Substrates for Opto‐Electronic Applications - Yuting Spiegelhoff; Filip Zemajtis; Elaheh Kheirandish; Olivier Grauby; Daniel Ferry; Roland J.‐M. Pellenq; Konstantin Sobolev; Nikolai Kouklin (Advanced Electronic Materials, 2023)
Abstract In the present study, polycrystalline films of layered zinc phosphate hydrate are produced by a facile, low‐temperature single‐step hydrothermal fabrication method on top of Cu metal substrates. Despite containing structural water, the as‐grown films remain crystalline, chemically stable, and electrically conductive. The photoluminescence spectrum obtained at room‐temperature reveals the presence of a spectrally narrow, high‐intensity ultraviolet band that consists of two Gaussian peaks at ≈377 and 383 nm and a UV‐to‐visible peak emission intensity ratio of ≈5.3. The electrical charge‐transport properties remain Ohmic for electric fields of up to ≈2 kV m−1 and temperature (T) range of ≈223–368 K. The electrical conductivity is further found to vary exponentially with the inverse temperature, and the thermal activation energy, Ea is 285 ± 8 meV. A moderate UV‐vis photoconduction effect is registered and assigned to light‐assisted electronic transitions that involve near‐band edge defect states. This study can potentially open a door to the engineering and deployment of water‐based compounds with advanced, semiconducting‐like attributes in short‐wavelength opto‐electronic devices.